Alcohol outlets, social disorganization, and non-violent crimes in urban neighborhoods - Snowden, Aleksandra J. (Journal of crime and justice, 2017)
Many studies show an association between alcohol outlets and violence, though fewer consider non-violent crime. We add to this literature using block group data from Milwaukee, Wisconsin, to explore whether (1) on- and off-premise alcohol outlet density is related to thefts from vehicles and vandalism and (2) social disorganization moderates these associations. Using spatially informed regression models, we found positive effects of on-premise alcohol outlet density on thefts from vehicles. We also found positive effects of on- and off-premise alcohol outlet density on vandalism. Social disorganization was not a consistent moderator of these associations.